Activation of Insulin Signal Transduction Pathway and Anti-diabetic Activity of Small Molecule Insulin Receptor Activators - Qureshi, Sajjad A.; Ding, Victor; Li, Zhihua; Szalkowski, Deborah; Biazzo-Ashnault, Dawn E.; Xie, Dan; Saperstein, Richard; Brady, Edward; Huskey, Su; Shen, Xiaolan; Liu, Kun; Xu, Libo; et al. (The Journal of biological chemistry, 2000)
We recently described the identification of a non-peptidyl fungal metabolite (l-783,281, compound 1), which induced activation of human insulin receptor (IR) tyrosine kinase and mediated insulin-like effects in cells, as well as decreased blood glucose levels in murine models of Type 2 diabetes (Zhang, B., Salituro, G., Szalkowski, D., Li, Z., Zhang, Y., Royo, I., Vilella, D., Diez, M. T., Pelaez, F., Ruby, C., Kendall, R. L., Mao, X., Griffin, P., Calaycay, J., Zierath, J. R., Heck, J. V., Smith, R. G. & Moller, D. E. (1999) Science 284, 974–977). Here we report the characterization of an active analog (compound 2) with enhanced IR kinase activation potency and selectivity over related receptors (insulin-like growth factor I receptor, epidermal growth factor receptor, and platelet-derived growth factor receptor). The IR activators stimulated tyrosine kinase activity of partially purified native IR and recombinant IR tyrosine kinase domain. Administration of the IR activators to mice was associated with increased IR tyrosine kinase activity in liver.In vivo oral treatment with compound 2 resulted in significant glucose lowering in several rodent models of diabetes. In db/db mice, oral administration of compound 2 elicited significant correction of hyperglycemia. In a streptozotocin-induced diabetic mouse model, compound 2 potentiated the glucose-lowering effect of insulin. In normal rats, compound 2 improved oral glucose tolerance with significant reduction in insulin release following glucose challenge. A structurally related inactive analog (compound 3) was not effective on insulin receptor activation or glucose lowering in db/db mice. Thus, small molecule IR activators exert insulin mimetic and sensitizing effects in cells and in animal models of diabetes. These results have implications for the future development of new therapies for diabetes mellitus.